Legal Considerations Of Individual Companies As A Choice Of Current Form Of Business Entity (Case Study Of Individual Company R) - Naufal Viansa Fadhlurrahman; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
As stated in Article 28D paragraph (2) of the 1945 Constitution which reads that everyone has the right to work and to get an imbalance and fair and proper treatment in work relations. The verse can be used as the basis that everyone has the right to work, Humans themselves as economic beings act as agents who carry out economic actions to meet their needs. One form of meeting these needs is to do business. The purpose of this study is to explain the existence of a new form of business entity, namely an individual company which is a new form of business entity which is a legal entity in accordance with Law Number 11 of 2020 concerning Job Creation (cipta kerja). In this study, I raised the formulation of the problem how the form of individual business entities compared to other business entities at this time. The author takes a sample from the practice of company R. So, the second formulation is How an sole proprietorship company can be the right choice for an sole proprietorship R still has several obstacles in practice, especially the form of business problems, as well as the role of a notary in the formation of a form of business entity. The method used in this research is juridical-normative. The results of this study indicate that an individual company can be the preferred form of business entity for a sole proprietorship R.